Physical Therapy–Related Child Outcomes in School: An Example of Practice-Based Evidence Methodology. Issue 1 (2016) - Effgen, Susan K.; McCoy, Sarah Westcott; Chiarello, Lisa A.; Jeffries, Lynn M.; Bush, Heather
Abstract : Purpose: To describe the use of practice-based evidence research methodology in a prospective, multisite observational study to investigate changes in students' participation in school activity, self-care, posture/mobility, recreation/fitness, and academic outcomes, and the relationships of these changes to characteristics of school-based physical therapy. Methods: One hundred nine physical therapists completed the training and data collection and 296 students, 5 to 12 years of age (mean age = 7.3 years) had 6 months of complete data. Therapists completed individualized (Goal Attainment Scaling) and standardized (School Function Assessment) outcome measures for students at the beginning and end of the school year and during the year collected weekly data on services to and on behalf of the students. Summary: This research design enabled the investigation of complex research questions related to school-based practice. The findings of this study, to be reported later, should influence school-based therapy by providing guidance related to what activities, interventions, and services influence student outcomes. Abstract : The design and methods of an investigation of complex research questions related to school-based practice are presented. The findings of this study will be reported later and should provide guidance for activities, interventions, and services that influence student outcomes.